Analysis of the Implementation of Early Childhood Education in Ceria PAUD and Sekar Bangsa PAUD - Rahmah Rahmah; Raihanah Raihanah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
This study aims to analyze how early childhood education is implemented at Ceria PAUD and Sekar Bangsa PAUD. The research method used is a qualitative method and data collection techniques using observation, interviews and documentation. The data that has been collected is then analyzed using the Miles and Hubberman model which consists of data reduction, data display and data verification. The results of the study showed that Sekar Bangsa PAUD in its learning activities was interspersed with Al-Qur'an reading and writing materials and circumcision dhuha prayers. PAUD Sekar Bangsa integrates reading and writing the Koran and circumcision prayers as additional material, while PAUD Ceria is more flexible in preparing material. These different approaches can affect the effectiveness of learning. From a sociological point of view, the differences between the two can also be seen from the cultural and religious background of the community where both are located. The use of the classical method is used by both of them when teaching students who are in the beginner class, namely children aged 2-4 years. Meanwhile, they use the center method to teach children who are already in small A class and large A class. Consideration of the center method used because of the level of child development. Other methods that are often used are singing, telling stories, interpersonal methods. This research contributes to studying the variety of learning in various PAUD so that it can provide new information to education activists at the PAUD level.